2020
DOI: 10.1096/fasebj.2020.34.s1.04750
|View full text |Cite
|
Sign up to set email alerts
|

SASP from lung senescent fibroblasts induces immunesenescence and fibrosis

Abstract: Rationale Lung aging is characterized by a progressive functional impairment. One of the main features of aging is the accumulation of senescent cells, a phenotype that has been described in chronic lung diseases such as idiopathic pulmonary fibrosis (IPF). Senescent cells produce the senescence‐associated secretory phenotype (SASP), which is highly variable. Understanding SASP components would provide a new insight into the different pathologies of age‐related diseases. It is known that SASP has an effect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The SASP also seems to contribute to immune senescence in IPF. IPF patients have reduced numbers of NK cells in the lung with an impaired phenotype that appears to be controlled by the lung microenvironment through the SASP [97]. Importantly, the deficiency in cytotoxic NK activity could be one of the altered mechanisms perpetrating the accumulation of senescent fibroblasts and other cell types in IPF lungs.…”
Section: Saspmentioning
confidence: 99%
“…The SASP also seems to contribute to immune senescence in IPF. IPF patients have reduced numbers of NK cells in the lung with an impaired phenotype that appears to be controlled by the lung microenvironment through the SASP [97]. Importantly, the deficiency in cytotoxic NK activity could be one of the altered mechanisms perpetrating the accumulation of senescent fibroblasts and other cell types in IPF lungs.…”
Section: Saspmentioning
confidence: 99%
“…The SASP also seems to contribute to immune senescence in IPF. IPF patients have reduced numbers of NK cells in the lung with an impaired phenotype that appears to be controlled by the lung microenvironment through the SASP [99]. Importantly, the deficiency in cytotoxic NK activity could be one of the altered mechanisms perpetrating the accumulation of senescent fibroblasts and other cell types in IPF lungs.…”
Section: Saspmentioning
confidence: 99%
“…More recent evidence (in an abstract form) showed that SASP released by IPF senescent fibroblast promoted senescence of pulmonary NK cells that, in turn, permitted the accumulation of senescent fibroblasts. Thereby creating a vicious cycle of persistent chronic inflammation [187]. Moreover, the decrease of NK cell numbers in IPF patients is associated with an imbalance of the Treg/Th17 axis.…”
Section:  Other Immune Cellsmentioning
confidence: 99%
“…Premature senescence can be induced by a variety of pro-aging stressors including redox imbalance, telomere shortening, and genomic instability [ 6 ]. Moreover, the adoption of a secretome known as the senescence associated secretory phenotype (SASP) results in the release of a plethora of cytokines, growth factors, and matrix metalloproteinases that drive pathologic lung remodeling and inflammation [ 7 ]. The involvement of senescence in PF is further supported by the use of senolytic drugs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%